Freak Performances : Dissidence in Latin American Theater - Santana, Analola (Book collections on Project MUSE., 2018)
"The figure of the freak as perceived by the Western gaze has always been a part of the Latin American imaginary, from the letters that Columbus wrote about his encounters with dog-faced people to Shakespeare's Caliban. The freak acquires greater significance in a globalized, neoliberal world that defines the "abnormal" as one who does not conform mentally, physically, or emotionally and is unable or unwilling to follow the economic and cultural norms of the institutions in power. Freak Performances examines the continuing effects of colonialism on modern Latin American identities, with a particular focus on the way it has constructed the body of the other through performance. Theater questions the representations of these bodies, as it enables the empowerment of the silenced other; the freak as a spectacle of otherness finds in performance an opportunity for re-appropriation by artists resisting the dominant authority. Through an analysis of experimental theater, dance theater, performance art, and gallery-based installation art across eight countries, Analola Santana explores the theoretical issues shaped by the encounters and negotiations between different bodies in the current Latin American landscape"--